UPAYA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN INTERAKTIF SISWA KELAS V A SDN 013 BULUH KASAP KECAMATAN DUMAI TIMUR KOTA DUMAI - Abdullah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low mathematics learning outcomes of fifth-grade students at SDN 013 Buluh Kasap Dumai. Out of 32 students, only 7 students achieved the Minimum Mastery Criteria (KKM) of 65. Therefore, the researcher conducted a classroom action research aimed at improving the mathematics learning outcomes of fifth-grade students at SDN 013 Buluh Kasap Dumai through the application of an interactive learning model. This research was conducted in February 2012. The subjects of the study were 32 students of class V-A at SDN 013 Buluh Kasap Dumai. The data used in this study included students’ learning outcomes, student activities, learning mastery, and teacher activities. The instruments used consisted of learning instruments (syllabus, lesson plans, and student worksheets) and data collection instruments (student activity observation sheets, teacher activity observation sheets, and achievement tests). The results showed that students’ learning mastery improved in each cycle. Based on the initial data, only 7 students (21.90%) achieved mastery. In the first cycle, the number of students who achieved mastery increased to 16 students (50.00%). In the second cycle, mastery further increased to 25 students (78.12%). It can be concluded that the mathematics learning outcomes of fifth-grade students at SDN 013 Buluh Kasap Dumai can be improved through the application of an interactive learning model.